ADVANCE-TBI study protocol: traumatic brain injury outcomes in UK military personnel serving in Afghanistan between 2003 and 2014 – a longitudinal cohort study. Issue 3 (21st March 2023) - Graham, Neil S N; Blissitt, Grace; Zimmerman, Karl; Friedland, Daniel; Dumas, Marc-Emmanuel; Coady, Emma; Heslegrave, Amanda; Zetterberg, Henrik; Escott-Price, Valentina; Schofield, Susie; Fear, Nicola T; Boos, Christopher; et al.
Abstract : Introduction: Outcomes of traumatic brain injury (TBI) are highly variable, with cognitive and psychiatric problems often present in survivors, including an increased dementia risk in the long term. Military personnel are at an increased occupational risk of TBI, with high rates of complex polytrauma including TBI characterising the UK campaign in Afghanistan. The ArmeD SerVices TrAuma and RehabilitatioN OutComE (ADVANCE)-TBI substudy will describe the patterns, associations and long-term outcomes of TBI in the established ADVANCE cohort. Methods and analysis: The ADVANCE cohort comprises 579 military personnel exposed to major battlefield trauma requiring medical evacuation, and 566 matched military personnel without major trauma. TBI exposure has been captured at baseline using a standardised interview and registry data, and will be refined at first follow-up visit with the Ohio State Method TBI interview (a National Institute of Neurological Disorders and Stroke TBI common data element). Participants will undergo blood sampling, MRI and detailed neuropsychological assessment longitudinally as part of their follow-up visits every 3–5 years over a 20-year period. Biomarkers of injury, neuroinflammation and degeneration will be quantified in blood, and polygenic risk scores calculated for neurodegeneration. Age-matched healthy volunteers will be recruited as controls for MRI analyses. We will describe TBI exposure across the cohort, and consider any relationship with advanced biomarkers of injury and clinical outcomes including cognitive performance, neuropsychiatric symptom burden and function. The influence of genotype will be assessed. This research will explore the relationship between military head injury exposure and long-term outcomes, providing insights into underlying disease mechanisms and informing prevention interventions. Ethics and dissemination: The ADVANCE-TBI substudy has received a favourable opinion from the Ministry of Defence Research Ethics Committee (ref: 2126/MODREC/22). Findings will be disseminated via publications in peer-reviewed journals and presentations at conferences.